Persepsi Masyarakat Desa Sekitar Gunung Sawal terhadap Konflik Manusia dan Macan Tutul Jawa - Raharja, Agung; Syartinilia; Ario, Anton (http://arl-faperta.ipb.ac.id/, 2025)
This research examines the community perception in the landscape of Sawal Mount Forest, the presence of the Javan leopard, and the conflict between the Javan leopard and local communities in the villages surrounding Sawal Mount in Ciamis Regency, West Java. It was conducted from July to September 2022 using a combination of field observation and interview methods with purposive sampling. The results of the interviews with 160 respondents indicated that 73 people (45%) were farmers and ranchers. This community activity on the use of forested landscape products was found to be related to the Javan leopard conflict. The respondents' level of education appears to be a significant factor in their understanding of the Javan leopard conflict. A negative view of the Javan leopard was expressed by the majority of respondents at the elementary school graduation level. This indicates a lack of comprehension and decision-making in addressing the Javan leopard conflict. It is well-documented that conflict is contingent upon the nature of one's occupation. In this study, 42 people acknowledged a negative perception of the Javan leopard. Of these, 26 people (62%) were farmers and breeders. This is postulated because farmers utilize forest landscape for crop cultivation, which can potentially give rise to conflict. Furthermore, the Javan leopard preys on livestock owned by the community, which can also give rise to community animosity.